2022
DOI: 10.14423/smj.0000000000001465
|View full text |Cite
|
Sign up to set email alerts
|

Association of an Early Interest in Orthopedic Surgery with Match Rate into Orthopedic Surgery

Abstract: Objectives: Orthopedic surgery residency is considered one of the most competitive specialties in which to match. Studies examining the factors associated with a successful match have neglected whether participation in an orthopedic interest group (OIG) improves the chances of orthopedic residency match. The goal of this study was to test the hypothesis that participation in the OIG would improve matching into an orthopedic surgery residency. Methods:We performed a retrospective cohort study between May 2017 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…5 In fact, Sephien et al found a statistically significant increase in orthopedic surgery Match rate in students who were members of their orthopedic interest group compared with nonmembers (odds ratio 3.43). 6 Participating in these groups can help students build relationships and network with potential mentors, which is vital for an applicant. Milner et al reported that students with mentors tend to have a higher Match rate into highly ranked residency programs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 In fact, Sephien et al found a statistically significant increase in orthopedic surgery Match rate in students who were members of their orthopedic interest group compared with nonmembers (odds ratio 3.43). 6 Participating in these groups can help students build relationships and network with potential mentors, which is vital for an applicant. Milner et al reported that students with mentors tend to have a higher Match rate into highly ranked residency programs.…”
mentioning
confidence: 99%
“…Student involvement in an orthopedic surgery interest group (OSIG) is an important component of the residency application and a successful Match 5 . In fact, Sephien et al found a statistically significant increase in orthopedic surgery Match rate in students who were members of their orthopedic interest group compared with nonmembers (odds ratio 3.43) 6 . Participating in these groups can help students build relationships and network with potential mentors, which is vital for an applicant.…”
mentioning
confidence: 99%